Digital Movement Opinion Against the Hashtag #KTTG20 on Twitter - Hizwa Naufal M, Hizwa Naufal; Filosa Gita, Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2023)
Analysis on the hashtag #KTTG20 with the period during the 2022 G20 Summit presidency. The phenomenon of the hashtag as a media campaign for the G20 Presidency event, Twitter users can cast opinions in the form of tweets and seek information via the hashtag #KTTG20. This research uses the Digital Movement Opinion (DMO) and the NVivo 12 Plus data processing application to analyze the issues and topics discussed at the G20. The results from this study indicate that eight major issues have massive quantities in the discussion of issues. This also divides social media users into two sides, the public, who are pros and cons with this activity. Apart from that, buzzer accounts are dominating, spreading information successively, and interacting with accounts that are considered to be the opposite of their group.